“Auditoría tributaria para verificar el cumplimiento de las obligaciones tributarias de la empresa Mega Inmobiliaria, ciudad de Riobamba, año 2018” - Aida Margoth, Guamán Padilla (2020)
TITLE: " Tax Audit to verify compliance with the Mega Inmobiliaria Company's tax obligations, the city of Riobamba, the year 2018" AUTOR: Aida Margoth Guamán Padilla ABSTRACT: This research work consists of a Tax Audit to verify compliance with the Mega Inmobiliaria Company's tax obligations, the city of Riobamba, the year 2018, to evaluate if it correctly complies with the obligations as established by legal regulations. The research project begins by describing the problem's approach, and the objectives are established to know the end that is pursued. Besides, the importance of tax matters is justified. In the theoretical framework, the company's antecedents, the foundation of concepts related to the research topic of different authors, which are respectively cited, are disclosed. The research method that was used is inductive, allowing to determine the conclusions regarding the objectives proposed in the research. The type of research is documentary and field because it allowed the analysis of the entity's data, the approach of the research is quantitative since numerical data, and compliance dates were verified, the population is made up of the entity's collaborators with their respective documentation. In the audit, the three phases are defined: planning, execution, and communication of results and their importance, concerning the results and discussion, the procedures and audit techniques were applied, as well as the norms and tax laws in order to verify the degree of compliance with the obligations of the company concerning the Tax Administration and finally a report is issued in which it will contain conclusions and recommendations based on the findings found during the audit examination.